(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Environment and its integration are recognized as priorities at all governance levels, however practice reveals gaps at the local (municipal) level. Municipal environmental policy planning (EPP), implementation and monitoring is not studied sufficiently and discussed. Without understanding of disciplinary planning there are risks of qualitative integrative planning. The article discusses EPP development in Latvian municipalities during last 18 years period starting from Local Agenda 21 initiatives to integrated urban environment planning. The article summarizes EPP experience based on document studies and survey. It includes overview of EPP driving forces, content and integration analysis, institutional and public participation issues, outlines needs for further studies. Taking into account that EPP exist in less than 5 % of local governments, what is contrasting to practice elsewhere in Europe, the intention of the article is to facilitate discussion about EPP necessity and opportunities in Latvia.